Augmentation of NKT and NK cell-mediated cytotoxicity by peptidoglycan monomer linked with zinc - Ines Mrakovcic-Šutic; Biserka Radoševic-Stašic; Marija Šimin; Damir Muhvic; Daniel Rukavina (Mediators of Inflammation)
Background: Peptidoglycan monomer (PGM), which was originally prepared by biosynthesis from culture fluids of penicillin-treated Brevibacterium divaricatum, is an immunostimulator, the activities of which might be improved by addition of zinc (Zn) to the basic molecule.